Public Enterprises and Structural Adjustments in Sub-Saharan Africa: Some Lessons to be Learned - Aïhounhin, Parfait; Kérékou, H. Séphora; Aïtchédji, Codjo; Su, Zhan (Journal of Comparative International Management)

(untitled) (Management Futures, 2016)
For public choice and agency theorists, the poor performance of public enterprises is caused by inefficient policies and by managers who do not care about public interests. These managers and administrative officials are supposed to maximize their organizations' utility rather than their own personal ones. To draw attention of stakeholders on what they do and how they do it, we have adopted a research methodology using documentary sources and secondary data to investigate, through the why, who, when, where and how of structural adjustment through privatization in Africa.